Full Financial Inclusion (Ffi): A Pre-Requisite for Inclusive Economic Development in Nigeria - Bertram, O. A; Nwankwo, S.N.P.; Onwuka, Ifeanyi Onuka (Advances in Social Sciences Research Journal, 2016)
This study identified full financial inclusion as a prerequisite for inclusive economic development in Nigeria. The study utilized descriptive survey method that entails the use of questionnaire to generate data from stakeholders in financial inclusion, such as Banks, Insurance, Regulators, and Telecom firms providing every household with access to a suite of modern financial services, including savings, credit, insurance, and payments, as well as sufficient education and support to help customers make good decisions for themselves. Financial inclusion has continued to assume increasing recognition across the globe among policy makers, researchers and development oriented agencies. The world over and especially in developing countries, governments are working on various strategies and regulatory framework to ensure they reach all that are excluded from financial services. Access to financial services will mobilize greater household savings, marshal capital for investments, expand the class of entrepreneurs and enable more people to invest in themselves and families. Financial inclusion offers incremental and complementary solutions to tackle poverty, to promote inclusive development and to address Millennium Development Goals (MDGs). It aims at drawing the unbanked population into the formal financial system so that they have the opportunity to access financial services ranging from savings, payment, and transfers to credit and insurance. The result of the study reveals that financial inclusion is a bold step towards inclusive economic development. The paper concludes that all initiatives that make formal financial services available, accessible and affordable to all segments of the population should be encouraged to achieve inclusive economic development.